Capturing the Current-Overpotential Nonlinearity of Lithium-Ion Batteries by Nonlinear Electrochemical Impedance Spectroscopy (NLEIS) in Charge and Discharge Direction - Ernst, Sabine; Heins, Tom Patrick; Schlüter, Nicolas; Schröder, Uwe (Frontiers in Energy Research, 2019)
In this paper, a Nonlinear Electrochemical Impedance Spectroscopy (NLEIS) method is presented that allows capturing the nonlinearity of current and overpotential of a lithium-ion battery individually in charge and discharge direction. A DC bias is applied to the battery to shift its operating point to the nonlinear region of current and overpotential. An alternating current of a low amplitude (AC) is simultaneously superimposed in order to investigate the system additionally in the time domain. NLEIS cell spectra and selected electrode-resolved NLEIS spectra are recorded as a function of state of charge and temperature. Furthermore, Distribution of Relaxation Times (DRT) plots obtained from EIS measurements provide information, which electrochemical processes correlate with the occurrence of nonlinear distortions of current and overpotential. Moreover, the occurrence of overpotentials and their degree of nonlinearity at cathode and anode as a function of the state of charge are determined by current pulse measurements.